1967
DOI: 10.1161/01.cir.35.4.745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aminophylline on Urinary Excretion of Epinephrine and Norepinephrine in Man

Abstract: The excretion of catecholamines and the changes in plasma concentration of free fatty acids during aminophylline administration were explored. The relationships between cardiac arrhythmia, cardiac rate, and change in blood pressure under the conditions of these experiments were defined. Eighteen experiments were performed on eight volunteers. Blood pressures and heart rates before and during aminophylline infusion were recorded at frequent intervals, and urine and blood were collected during the control and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1974
1974
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…The findings are consistent with reports that theophylline increased circulating levels of catecholamines. 10,11,13 The increases in plasma catecholamine concentrations correlated with the doserelated increases in HR observed during their study, supporting the hypothesis that the cardiovascular effects of theophylline may be mediated in part by the beta-adrenergic system.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The findings are consistent with reports that theophylline increased circulating levels of catecholamines. 10,11,13 The increases in plasma catecholamine concentrations correlated with the doserelated increases in HR observed during their study, supporting the hypothesis that the cardiovascular effects of theophylline may be mediated in part by the beta-adrenergic system.…”
Section: Discussionsupporting
confidence: 61%
“…13 Tachycardia during theophylline intoxication occurs by a direct effect of theophylline on the sinus node, an increase in sympathetic nervous system activity, or an increase in catecholamines. 10,13 In this study, plasma concentrations of catecholamines increased from baseline values after administration of aminophylline. The findings are consistent with reports that theophylline increased circulating levels of catecholamines.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Failure to recover normal cardiac function after cardiopulmonary bypass correlates well with the inability to resynthesize normal levels of ATP. 14 7,8 However, this may be a consequence of the loss of ATP precursors rather than…”
mentioning
confidence: 99%
“…Cross-tolerance developed to isoprenaline when the guinea-pig was pretreated with adrenaline and also to aminophylline when the animals were pretreated with isoprenaline. The aminophylline experiments may not indicate whether tolerance is specific and/or non-specific, since aminophylline can be regarded as an indirectly acting sympathomimetic amine because it causes an increase in the release of endogenous catecholamines into the blood circulation (Atuck, Blaydes, Westervelt & Wood, 1967;Westfall & Fleming, 1968;Peach, 1972;Wooten, Thoa, Koplin & Axelrod, 1973 metic amines may also act in a way similar to aminophylline, since adrenaline inhibits phosphodiesterase activity (Hitchcock, 1973). Conolly et al (1971 reported that in guineapigs, the mortality from histamine-induced bronchospasm was higher in groups which had been pretreated with sympathomimetic amines than in groups which had been pretreated with saline.…”
Section: Cross-tolerance Studiesmentioning
confidence: 99%